The effects of eccentric, velocity-based training on strength and power in collegiate athletes - Dolezal, S. M.; Llewellyn, T. L.; Frese, D. L. (International Journal of Exercise Science, 2016)
The purpose of this study was to determine if combining velocity-based training with eccentric focus (VEB) and velocity-based training (VBT) results in power and strength gains. Nineteen men and women collegiate track and field athletes participated in this study. The subjects completed a 12-week intervention with either a VEB program or a VBT program. To determine the effectiveness of each program, the subjects completed four exercise tests before and after the training period: vertical jump, medicine ball put test, 1RM projected bench press and 1RM projected squat. There were no significant differences between the VBT results and the VEB results. However, there were significant improvements between the pre-test and post-test measures for each group. There were increases in 1RM projected squat for VEB men, VBT men, and VBT women. There were also significant improvements in the VEB male vertical jump and medicine ball put test pre- to post- intervention. For track and field athletes, both programs may result in strength and power gains, however, the results cannot be used to conclude that one resistance training program is superior.